2014
DOI: 10.1016/j.enbuild.2013.11.083
|View full text |Cite
|
Sign up to set email alerts
|

On the effect of material uncertainties in envelope heat transfer simulations

Abstract: The accuracy of energy simulation codes is considerably increasing and it follows that the inputs need to be properly defined and technically characterized. Despite the vast research on uncertainty and sensitivity analysis, little is known about the extent to which a single thermophysical property affects the simulation outcomes. This information can guide the manufacturers of building materials towards improved quality controls and the energy modelers to deeply investigate the input data. This study focuses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…and building materials manufacturers to ensure the minimum deviation as possible between designed and real building energy performance, in order to achieve the Union's 2020 20% headline. Prada et al [4] showed that, among the thermo physical properties of the building envelope, the uncertainty concerning thermal conductivity as input data for energy simulation is what mostly affects the final output accuracy during the design phase concerning heat losses, both outward during winter and inward during summer. Just to evaluate the as-built performance of buildings concerning the U-values of the envelope, in the last 5 years several researchers, other than the authors, used quantitative ITT leading to interesting results.…”
Section: Introductionmentioning
confidence: 99%
“…and building materials manufacturers to ensure the minimum deviation as possible between designed and real building energy performance, in order to achieve the Union's 2020 20% headline. Prada et al [4] showed that, among the thermo physical properties of the building envelope, the uncertainty concerning thermal conductivity as input data for energy simulation is what mostly affects the final output accuracy during the design phase concerning heat losses, both outward during winter and inward during summer. Just to evaluate the as-built performance of buildings concerning the U-values of the envelope, in the last 5 years several researchers, other than the authors, used quantitative ITT leading to interesting results.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the uncertainty of simulation predictions concluded that the reliability of simulation outcomes depends on the accuracy and precision of input data, simulation models and the skills of the energy modeller [43][44][45][46]. An estimation of the uncertainty introduced by each of the aforementioned factors can help to increase the awareness of the results reliability.…”
Section: Building Modelling Simulation and Uncertaintymentioning
confidence: 99%
“…Hopfe and Hensen investigated the possibility of supporting design by applying uncertainty analysis in building performance simulation [42]. Prada et al, studied the effect of uncertain thermophysical properties on the numerical solutions of the heat equation, analysing the difference between Conduction Transfer Functions (CTF) and Finite Difference (FD) model predictions [46]. Mirsadeghi et al, reviewed the uncertainty introduced by the different external convective heat transfer coefficient models in building energy simulation programs [49].…”
Section: Building Modelling Simulation and Uncertaintymentioning
confidence: 99%
“…Moreover, the simulation set was performed using a unique algorithm for the model calculation. It is known that some of the calculation assumptions on heat transfer processes, such as convection, radiation, conduction or heat balances may have implications for the results, as assessed in [33,34].…”
Section: Climatementioning
confidence: 99%